Influence of Heat Treatment of Nickel–Titanium Instruments on Cyclic Fatigue Resistance in Simulated Curved Canals - Campos, Gustavo Oliveira; Fontana, Carlos Eduardo; Vieira, Victor Talarico Leal; Elias, Carlos Nelson; de Martin, Alexandre Sigrist; Bueno, Carlos Eduardo da Silveira (European Journal of Dentistry, 2022)
Objective The aim of this study was to compare the cyclic fatigue of heat-treated and non-treated instruments.Materials and Methods Twenty instruments with and without heat treatment from Bassi Logic were evaluated (n = 10). All instruments were subjected to dynamic cyclic fatigue through continuous rotations inside a stainless-steel tube (1.4-mm diameter, 9-mm curvature with 6-mm radius, and 90° angle) using a custom-made device, which performed 1 axial oscillation every 2 seconds with an amplitude of 3 mm, powered by a torque-controlled motor (Silver Reciproc, VDW, Germany), with speed adjusting to 950 rpm and torque to 4 N, according to manufacturer's guidance. The groups were compared using the Mann–Whitney test.Result The fracture time of the heat-treated instruments (97.20 ± 39.94 second and non-treated instruments (14.30 ± 6.78 seconds had statistical differences [p < 0.05]). Heat-treated instruments were 6.8 times more resistant to fatigue than non-treated instruments (p < 0.05).Conclusion Heat treatment provides increased fatigue resistance of NiTi alloy with the same design.
Keywords: endodontics; kinematics; mechanical stress; nitinol; rotation